Fundamentals of database systems - Elmasri, Ramez A.; Navathe, Shamkant B. (Boston : Pearson/Addison Wesley, 2007)
This edition combines clear explanations of database theory and design with up-to-date coverage of models and real systems. It features excellent examples and access to Addison Wesley's database Web site that includes further teaching, tutorials and many useful student resources.
Databases and Database Users -- Database System Concepts and Architecture -- Data Modeling Using the Entity-Relationship (ER) Model -- Enhanced Entity-Relationship (EER) Modeling -- The Relational Data Model and Relational Database Constraints -- The Relational Algebra and Relational Calculus -- Relational Database Design by ER- and EER-to-Relational Mapping -- SQL-99: Schema Definition, Constraints, Queries and Views -- Introduction to SQL Programming Techniques -- Functional Dependencies and Normalization for Relational Databases -- Relational Database Design Algorithms and Further Dependencies -- Practical Database Design Methodology and Use of UML Diagrams -- Disk Storage, Basic File Structures, and Hashing -- Indexing Structures for Files -- Algorithms for Query Processing and Optimization -- Physical Datebase Design and Tuning -- Introduction to Transaction Processing Concepts and Theory -- Concurrency Control Techniques -- Database Recovery Techniques -- Concepts for Object Databases -- bject Database Standards, Languages, and Design -- Object-Relational and Extended-Relational Systems -- Database Security -- Enhanced Data Models for Advanced Applications -- Distributed Databases and Client-Server Architectures -- Web Database Programming Using PHP -- XML: Extensible Markup Language -- Data Mining Concepts -- Overview of Data Warehousing and OLAP -- Emerging Database Technologies and Applications -- Appendix a Alternative Diagrammatic Notations for ER Models -- Appendix B Parameters of Disks -- Appendix C Overview of the QBE Language -- Appendix D Overview of the Hierarchical Data Model -- Appendix E Overview of the Network Data Model.
Includes bibliographical references (pages 1067-1095) and index.
Keywords: DATABASE MANAGEMENT